Garden Based Learning Strategy Instilling Environmental Consciousness in Early Childhood - Herwina, Herwina (Indonesian Journal of Early Childhood Education Studies, 2018)
Serious environmental problems being faced today is the problem of environmental quality degradation. Global natural environment faces an increasing pressure as the exploitation of natural resources is not controlled. Then the awareness is need to be grown to maintain and preserve the environment through education. At school, the knowledge and values ​​of environmental awareness can be introduced to early childhood so that the child's confidence about the value will be getting stronger. Environmental awareness should be developed in early childhood education through appropriate learning strategy. Early childhood is an active learner and learning through concrete case and very happy to be outside the classroom to do activities. Therefore, using garden based learning strategy or outside the classroom learning strategy by using the land or the school garden with the aim of instilling environmental awareness to the children is highly appropriate to be used. The garden based learning aims to develop some life skills and multiple intelligences and to generate the early children’s awareness to love the environment.